Biopolitique et autobiographisme. Les deux malades de Franz Joseph Gall - Sawala, Wojciech (Studia Romanica Posnaniensia, 2018)
The aim of this article is, on the one hand, to show Franz Joseph Gall as an important figure for setting up the ideological framework for modern biopolitics and, on the other, to look at the literary traces of his personal engagement in this endeavour. In the first part, we place his thought in the ideological context of the 18th and 19th century; the second one analyses the images of the patients created by the author, in order to show their different configurations: while some appear as reduced to the role of homo sacer (Giorgio Agamben’s term), others are inscribed in a dignifying discourse. We look at the political implications of this situation.